2003
DOI: 10.1038/ncb978
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sprouty4 suppresses Ras-independent ERK activation by binding to Raf1

Abstract: The signalling cascade including Raf, mitogen-activated protein kinase (MAPK) kinase and extracellular-signal-regulated kinase (ERK) is important in many facets of cellular regulation. Raf is activated through both Ras-dependent and Ras-independent mechanisms, but the regulatory mechanisms of Raf activation remain unclear. Two families of membrane-bound molecules, Sprouty and Sprouty-related EVH1-domain-containing protein (Spred) have been identified and characterized as negative regulators of growth-factor-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
139
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 29 publications
9
139
0
Order By: Relevance
“…Immunoblot analysis was carried out by using antibodies for c-Myc, GAPDH (Santa Cruz Biotechnology, Delaware, CA, USA), phospho-ERK1,2 (Thr 202, Tyr 204), ERK-1,2, phospho-Akt (Ser 473), Akt (Cell Signaling, Beverly, MA, USA) and Spred-1 (Wakioka et al, 2001) as described (Sasaki et al, 2003). Immunohistochemistry was performed on 5 mm sections of formalin-fixed, paraffin-embedded tissue.…”
Section: Immunoblot and Immunohistochemistrymentioning
confidence: 99%
“…Immunoblot analysis was carried out by using antibodies for c-Myc, GAPDH (Santa Cruz Biotechnology, Delaware, CA, USA), phospho-ERK1,2 (Thr 202, Tyr 204), ERK-1,2, phospho-Akt (Ser 473), Akt (Cell Signaling, Beverly, MA, USA) and Spred-1 (Wakioka et al, 2001) as described (Sasaki et al, 2003). Immunohistochemistry was performed on 5 mm sections of formalin-fixed, paraffin-embedded tissue.…”
Section: Immunoblot and Immunohistochemistrymentioning
confidence: 99%
“…Phosphorylated Spry can either bind to Grb2, thus competitively inhibiting the recruitment of Grb2-Sos complex (Hanafusa et al, 2002) or sequester c-Cbl, which would otherwise mediate internalization of activated RTKs Rubin et al, 2003). In addition, Spry4 may act downstream of Ras resulting in suppression of VEGFRmediated ERK activation in an Ras-independent manner by binding to Raf1 directly (Sasaki et al, 2003). This function appears not to require the conserved Tyr 55 and binding to Raf1 is through its highly conserved carboxy-terminal cysteine-rich domain (commonly called the Sprouty box).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological functions of mSproutys, however, have not been well established. We and others have shown that mSprouty2 and mSprouty4 inhibit vascular endothelial growth factor-induced extracellular signalregulated kinase (ERK) activation and vascular branching and sprouting of vessels (Impagnatiello et al, 2001;Lee et al, 2001;Cabrita and Christofori, 2003;Sasaki et al, 2003). Since mSproutys inhibit not only the proliferation but also the migration of endothelial cells (Lee et al, 2001) as well as Hela cells (Yigzaw et al, 2001), mSproutys may modulate cytoskeletal organization.…”
Section: Introductionmentioning
confidence: 99%